Electrical Performance of HTV Silicone Rubber under Different Fillers and Filler Loadings - Ilhan, Suat; Tuzun, Didem; Ozdemir, Aydogan (IEEE, 2019)
This paper presents tracking and erosion performance of high temperature vulcanizing (HTV) silicone rubber (SIR) materials for different filler loadings. Different concentrations of alumina trihydrate (ATH) filler particles of $3.6 \mu\mathrm{m}$ median size and silica (SiO 2 ) filler particles of $4 \mu\mathrm{m}$ median size are considered together with HTV-SIR material. Tracking and erosion performance of the compositions were evaluated by using standard inclined plane (IP) tracking and erosion tests, according to IEe 60587 standard. IP tests are performed at 3.5 kV power frequency (50 Hz) constant test voltages, for 0.3 ml/min contamination flow rate, at an ambient temperature of $\pmb{23}\pm \pmb{2}\ {}^{\circ}\mathbf{C}$ , and for six hours of test periods. Time-to-failures, eroded masses, and leakage currents of HTV-SIR filled with ATH and silica particles are investigated for different filler concentrations.